The results of a complex study of the Turchu limestone hollow (polje). Western Georgia, Caucasus - Zaza Lezhava; Kukuri Tsikarishvili; Lasha Asanidze; Nino Chikhradze; Tamazi Karalashvili; Davit Odilavadze; Avtandil Tarkhnishvili (European Journal of Geography)
Based on the complex studies (geographical-geological, karst-speleological, and geophysical studies), conducted by the authors in the study area, karst forms such as sinkholes and ponors were identified, the width (2-17 m) of the Quaternary deposits located on the limestones were determined, the average and maximum discharges of the streams flowing on the bottom of the hollow were calculated. Studies have also shown that relatively heavy rains and snowmelt periodically flood the relatively low, western part of the hollow and create a temporary lake that soon dries up through the ponors at the bottom of the hollow, where the water stream are discharged. The closed shape of the Turchu hollow the limestone bottom covered with Quaternary deposits and the events described above indicate the corrosive origin of the hollow, which has been practically confirmed by our georadiological and electrometric studies. It is notable that the role of tectonic movements in the origin of the hollow along with the corrosive processes, which had a periodic character, and together with the uplifting of the area caused the lowering of the levels of underground waters and, consequently, the activation of karst processes.